Participamos conversando sobre nuestros juegos preferidos - Perez Rodriguez, Martha Mirella (2020)
The session entitled "We participate in conversations about our favorite games" was developed in the area of Communication taking into account the competence: Communicates in its mother tongue, as well as the ability: Infers and interprets information from the oral text and performance: Participates in various Oral exchanges asking questions about what you are interested in knowing, giving answers and making comments related to the topic. Resorts to norms and models of courtesy according to the sociocultural context In the development of the session, motivational and challenging activities were applied that encouraged achievement and active participation through dialogue with the purpose that students express what they feel and think. It was taken into account pedagogical processes such as motivation and exploration of previous knowledge, problematization, construction of learning and information processing, evaluation and transfer in the didactic processes of the área The learning strategies were to use the puzzle, the dynamics of the game and the activities consisted of forming four groups of 5 members each group, to assemble the puzzle and put into practice the game entitled "hawk and chicks", these activities were consistent to the interests and needs of the students of the second grade of primary education.